In search of cheap labour in Europe: working and living conditions of posted workers - Cremers, Jan (Brussels, 2011)
"The cross border provision of services with posted workers is an integral part of the economic freedoms in the EU internal market. In the best case this provision is a logical part of a genuine division of labour at European scale between contractors and specialised subcontractors. In the worst case the cross border provision of services falsely can be used as a method to recruit cheap temporary labour. The EU Posting Directive, established in the mid 1990s, tried to settle posting rules that could guarantee the rights of posted workers within the territory where the work was pursued. Starting point was that a foreign employer, who temporarily delivers services, with workers posted, had to respect a large part of the applicable labour standards in the host country. CLR Studies 6 is dedicated to an analysis of the theory and practice of the functioning of the posting rules in 12 European countries. The experts’ focus was on the practical experiences of compliance authorities, labour inspectors and other controlling bodies. One of the main conclusions of this practical evaluation is that the use of the posting mechanism ranges from normal and decent long-established partnership between contracting partners to completely fake letter box practices of labour-only recruitment."